Effectiveness of a Web-Based Guided Inquiry Platform on Dynamic Fluid Material to Improve Students’ Critical Thinking Skills - Barakah, Nadia; Suyidno, Suyidno; Mahtari, Saiyidah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study investigates the improvement of students’ critical thinking skills following the implementation of a web-based learning platform integrated with a guided inquiry model on dynamic fluid topics. The study employed a pre-experimental one-group pretest–posttest design involving 30 Grade XI students at a public senior high school in Banjarmasin, Indonesia. Students’ critical thinking skills were measured using an essay-based test developed based on Ennis’ critical thinking framework, covering interpretation, analysis, inference, evaluation, and explanation. The maximum possible score was 100, with student responses scored using an analytical rubric and converted to a percentage scale. Data were analyzed using normalized gain (N-Gain) and a paired-sample t-test. The results showed an increase in the mean score from 3.82 on the pretest to 79.69 on the posttest, with an N-Gain of 0.74 (high category). The paired-sample t-test indicated a statistically significant difference between pretest and posttest scores (p < 0.05), suggesting a substantial improvement in students’ critical thinking skills after the intervention. Improvements were observed across all critical thinking indicators, particularly in analysis and evaluation. Although the findings indicate positive learning gains, the use of a one-group pretest–posttest design limits causal interpretation. Nevertheless, the results suggest that web-based guided inquiry learning has the potential to support the development of students’ critical thinking skills in physics learning, especially for abstract topics such as dynamic fluids.